2021
DOI: 10.1021/acs.jafc.0c07871
|View full text |Cite
|
Sign up to set email alerts
|

Multiomics Approach to Explore the Amelioration Mechanisms of Glucomannans on the Metabolic Disorder of Type 2 Diabetic Rats

Abstract: Type 2 diabetes (T2D) is a worldwide epidemic associated with metabolic disorders and intestinal microbiota alterations. Polysaccharides have been considered to be beneficial to the prevention and alleviation of T2D. In the present study, ultra-performance liquid chromatography−triple-time-of-flight-based metabolomics and proteomics and 16S rRNA sequencing methods were employed to evaluate the effects of glucomannans from Dendrobium officinale stem, konjac, and Aloe vera leaves on host metabolism and intestina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 63 publications
(111 reference statements)
0
22
0
Order By: Relevance
“…While it is difficult to adjust to a different dietary intake of individual AA in large human trials, animal studies allow for such a standardization and, therefore, for a more precise identification of microbiota-derived BCAA in the circulation. Several studies addressing the relationship between gut microbiota, circulating metabolites, and metabolic health were performed in animal models of obesity (mice fed a high-fat diet) [48,74] or diabetes (rats fed a high-fat diet and treated with streptozotocin) [75] (Table 2). In all models, serum BCAAs were significantly elevated and could be regarded as serum biomarkers of obesity-related insulin resistance.…”
Section: Animal Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…While it is difficult to adjust to a different dietary intake of individual AA in large human trials, animal studies allow for such a standardization and, therefore, for a more precise identification of microbiota-derived BCAA in the circulation. Several studies addressing the relationship between gut microbiota, circulating metabolites, and metabolic health were performed in animal models of obesity (mice fed a high-fat diet) [48,74] or diabetes (rats fed a high-fat diet and treated with streptozotocin) [75] (Table 2). In all models, serum BCAAs were significantly elevated and could be regarded as serum biomarkers of obesity-related insulin resistance.…”
Section: Animal Studiesmentioning
confidence: 99%
“…HFD induced significant changes in the gut microbiota composition characterized by the increased Firmicutes to Bacteroidetes ratio but, at the genus level, the outcomes were quite heterogeneous. Pathway analysis based on the metabolite abundances [48,75] or PICRUSt analysis based on the gut microbiota composition [74] identified an increased BCAA biosynthesis pathway in the HFD groups. The BCAA degradation pathway was decreased in HFD-fed mice only in the study of Zeng et al [48] but not in the others.…”
Section: Animal Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, the amendatory gut microbiota could accelerate the fermentation of dietary KF to improve the SCFAs' concentration in the intestinal contents, thus ameliorating obesity and its-related complications ( 161 , 163 ). On the other hand, it is well known that increased circulating BCAA concentrations can deteriorate host glucose and lipid metabolism, and subsequently prognosticate future risk of developing insulin resistance and diabetes ( 169 ). Interestingly, a recent study has demonstrated that KGM treatment (160 mg kg −1 ) of type 2 diabetic rats for 4 weeks reduced the abundance of BCAA-producing bacteria and improved BCAA metabolism, further ameliorating host lipid metabolism and diabetes ( 169 ).…”
Section: Plant Extracts In Obesity: Potential Implication Of the Gut Microbiotamentioning
confidence: 99%
“…On the other hand, it is well known that increased circulating BCAA concentrations can deteriorate host glucose and lipid metabolism, and subsequently prognosticate future risk of developing insulin resistance and diabetes ( 169 ). Interestingly, a recent study has demonstrated that KGM treatment (160 mg kg −1 ) of type 2 diabetic rats for 4 weeks reduced the abundance of BCAA-producing bacteria and improved BCAA metabolism, further ameliorating host lipid metabolism and diabetes ( 169 ). In summary, KF might be a promising agent to prevent and to treat obesity, and the potential mechanism was associated with reprogramming gut microbiota and metabolism, especially decreasing BCAA-producing bacteria abundance ( Figure 6 ).…”
Section: Plant Extracts In Obesity: Potential Implication Of the Gut Microbiotamentioning
confidence: 99%